2006
DOI: 10.1258/002367706777611488
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory environments and rodents' behavioural needs: a review

Abstract: SummaryLaboratory housing conditions have significant physiological and psychological effects on rodents, raising both scientific and humane concerns. Published studies of rats, mice and other rodents were reviewed to document behavioural and psychological problems attributable to predominant laboratory housing conditions. Studies indicate that rats and mice value opportunities to take cover, build nests, explore, gain social contact, and exercise some control over their social milieu, and that the inability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(93 citation statements)
references
References 107 publications
2
86
0
5
Order By: Relevance
“…As the husbandry in our study differed slightly between the hydrocephalic and the control groups (Gattermann et al 2002), it remains unclear whether the hydrocephalus had any There have been numerous studies in mice and rats that showed how early husbandry can affect neurodevelopment. Impoverished living environments lead to impaired brain development (Balcombe 2006). We can exclude the possibility that this factor may have played a role in our study, as both the affected as well as the control groups were reared under comparable living conditions, with a high environmental complexity.…”
Section: Discussionmentioning
confidence: 99%
“…As the husbandry in our study differed slightly between the hydrocephalic and the control groups (Gattermann et al 2002), it remains unclear whether the hydrocephalus had any There have been numerous studies in mice and rats that showed how early husbandry can affect neurodevelopment. Impoverished living environments lead to impaired brain development (Balcombe 2006). We can exclude the possibility that this factor may have played a role in our study, as both the affected as well as the control groups were reared under comparable living conditions, with a high environmental complexity.…”
Section: Discussionmentioning
confidence: 99%
“…It is also necessary to know them during training of animals (Hasegawa et al, 2014) Knowledge about animal behavior is also applicable in the field of veterinary prevention in all categories of animals use. The design of animal fascilities should be in accordance with the behavioral forms typical for certain animal species (Balcombe, 2006). Therefore, it is not a surprise that today's legislation requires animals to be housed in a "naturalized" environment, as is the case of laying hens, for example, a cage should be equipped with things for climbing, hiding, poking about and plucking.…”
Section: Application Of Knowledge About Animal Behavior In Veterinarymentioning
confidence: 99%
“…It has been suggested by several researchers that tail-biting can be prevented Original Research by making changes in housing, changes in the animals' diet (mainly protein and mineral balance), and providing substrates (straw, compost, newspaper, ties), as well as eliminating atmospherically uncomfortable factors (high levels of ammonia, CO2, humidity, or low barometric pressure). 24,25,[27][28][29][30][31] Boredom is also a relevant factor in these circumstances. In rustic systems, where animal density is lower, sometimes rims, chains, or alfalfa branches are placed within enclosures as sources of entertainment for the animals, a situation which technified systems "cannot afford".…”
Section: Welfare Of Pigs In Rustic and Technified Farmsmentioning
confidence: 99%